Analysis of the Use of Discourse Cohesion Means of Speech Texts of the Regional Government of Jambi Province - Sri Wahyuni (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This research aims to describe the means of discourse cohesion and the use of discourse cohesion means in the speech text of the Jambi Province regional government at the plenary session on January 6 2016. The expected benefit of this research theoretically is that it can be used to develop theories about discourse, especially regarding the use of cohesion means in discourse speech text. Methodology: The method used in this research is a qualitative method with descriptive research type. This research data is in the form of a means of cohesion contained in discourse. Data was obtained by reading the entire discourse of the speech text and marking the found means of cohesion and recording them. Main Findings: The results of research in the speech text of the regional government of Jambi Province at the plenary session on January 6 2016 found that there were 9 types of cohesive devices, consisting of pronouns, substitutions, ellipsis, conjunctions, repetitions, synonyms, antonyms, hyponyms and collocations. It can be concluded that the most common means of cohesion are pronouns and conjunctions. So, from the results of the analysis that has been carried out, the text of the Jambi Province regional government's speech at the plenary session on January 6 2016 is included in the very cohesive category. Novelty/Originality of this study: From the results of this research, it can be seen that there has been progress, namely that 9 means of cohesion were found and no non-cohesive means were found. Meanwhile, previous research only found 8 means of cohesion and found several uses of non-cohesive means of cohesion.